Hypsagonus quadricornis ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Hypsagonus quadricornis (Valenciennes, 1829). Fourhorn Poacher. To 12 cm (4.7 in) TL (Tokranov and Orlov 2004). Northern Japan and Sea of Okhotsk, to Commander–Aleutian Chain, and Bering Sea (Mecklenburg et al. 2002), to northeastern Chukchi Sea as far north as 71°01’N, 164°52’W (Mecklenburg et al. 2016), to Puget Sound, Washington (Eschmeyer and Herald 1983). Benthic; depth: intertidal to 452 m (1,483 ft) (Mecklenburg et al. 2016). The species name is often attributed to Cuvier, but Valenciennes provided both the species name and the description; the full citation is Valenciennes in Cuvier & Valenciennes, 1829 (Sheiko 1993; see also Mecklenburg et al. 2002, Sheiko and Mecklenburg 2004). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 130, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...